PERAN SELF MANAGEMENT PRACTICES TERHADAP KEPUASAN KERJA KARYAWAN BANK PERKREDITAN RAKYAT - Muafi Muafi (University of Merdeka Malang, 2010)
Rural banking (Bank Perkreditan Rakyat BPR) had realized that self managementpract ices would give important cont ribut ion to the work sat isfact ion. This research invest igatedthe role of self management pract ices inf luencing work sat isfact ion for employees inrural banking (BPR). It was a survey research by survey research type. The respondents werethe employees in rural banking organizat ions in Magelang regency, Cent ral Java. The techniqueof sampling ut ilized purposive sampling. The number of sample, which required thecriteria to be examined, was 111 respondents. The technique of stat ist ics applied in thisresearch was part ial regression. The result of hypothesis examining explained that ; there wasplanning and goal set t ing inf luence to work sat isfact ion; there was access management influence to work sat isfact ion; there was catch up activit ies inf luence to work sat isfact ion; andthere was emot ion management inf luence to work sat isfact ion.